Hybrids of porphyrins and graphene oxide for biological applications - Monteiro, Ana Rita Rodrigues Vilares Cabral (2020)
Non-covalent hybrids between cationic porphyrins and graphene oxide (GO) have been acquiring an increasing importance in several biological applications due to their individual properties. Throughout this work, several tetracationic porphyrins were synthesized and non-covalently assembled to GO. As a consequence of their interaction, the typical absorption bands of the porphyrins were red-shifted and the fluorescence emission was quenched. The hybrids were further characterized by several techniques, such as Raman spectroscopy, Raman mapping and electron microscopy, to provide new molecular insights regarding their formation. Then, the non-immobilized porphyrins and the successful hybrids were tested as potential deoxyribonucleic acid (DNA) G-Quadruplex (G-Q) ligands, which has been pointed out as a promising strategy to promote telomerase inhibition in cancer therapies. The hybrid materials displayed a selective fluorescence recovery upon the addition of G-Q, resembling a “turn-off-on” fluorescence sensor that can be promising to distinguish G-Q structures from the common duplex DNA. Finally, all the non-immobilized porphyrins, GO and hybrids were tested as photodynamic therapy agents on T24 human bladder cancer cells by experiments in absence of light and by using blue light (BL) and red light (RL). None of the tested compounds displayed significant levels of cytotoxicity in the experiences performed in the absence of light. The obtained results suggest that the tested hybrids are less efficient than the non-immobilized porphyrins, both in the BL and RL experiments. Therefore, future studies require an optimization of the as-developed hybrids to increase their efficiency to PDT